A novel ALS-associated variant in UBQLN4 regulates motor axon morphogenesis - Brittany M Edens; Jianhua Yan; Nimrod Miller; Han-Xiang Deng; Teepu Siddique; Yongchao C Ma (eLife, 2017)
The etiological underpinnings of amyotrophic lateral sclerosis (ALS) are complex and incompletely understood, although contributions to pathogenesis by regulators of proteolytic pathways have become increasingly apparent. Here, we present a novel variant in UBQLN4 that is associated with ALS and show that its expression compromises motor axon morphogenesis in mouse motor neurons and in zebrafish. We further demonstrate that the ALS-associated UBQLN4 variant impairs proteasomal function, and identify the Wnt signaling pathway effector beta-catenin as a UBQLN4 substrate. Inhibition of beta-catenin function rescues the UBQLN4 variant-induced motor axon phenotypes. These findings provide a strong link between the regulation of axonal morphogenesis and a new ALS-associated gene variant mediated by protein degradation pathways.